The role of redox potential measurement in oak barrel wine maturation - Berovič, Marin (Array, 2019)
Redox potential measurement was efficiently used for monitoring the two-year maturation process of cultivar Blau Fränkisch wine in 225-L oak barrels. Redox potential of maturing wine was measured at six levels from the top to the bottom of the barrel. During the process of wine maturation, the formation and heterogeneity of redox layers, as well as the formation of various oxidoreductive zones were indicated. The end of barrel maturation process was represented with homogeneity of all redox zones where no differences in all measured levels were indicated.